2011
DOI: 10.1016/j.cub.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring “the Knowledge” of London's Layout Drives Structural Brain Changes

Abstract: SummaryThe last decade has seen a burgeoning of reports associating brain structure with specific skills and traits (e.g., [1–8]). Although these cross-sectional studies are informative, cause and effect are impossible to establish without longitudinal investigation of the same individuals before and after an intervention. Several longitudinal studies have been conducted (e.g., [9–18]); some involved children or young adults, potentially conflating brain development with learning, most were restricted to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
250
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(287 citation statements)
references
References 45 publications
(36 reference statements)
23
250
2
4
Order By: Relevance
“…This was a cross-sectional study and it does not really say anything about the causal link between this map learning and the good cognitive performance or the structural changes of the hippocampus in the brain, because those taxi drivers who managed well in tests might have had a larger hippocampus volume already from the beginning. However, Woollett and Maguire (2011) recently confirmed the findings in a longitudinal study showing that there is a causal link between cognitive training and structural changes of the brain. Similar associations between changes in brain structure after training has also been recently demonstrated by several other researchers and is nicely summarised by May (2011) and Simon, Yokomizo, and Bottino (2012).…”
Section: Lifespan Developmentsupporting
confidence: 67%
“…This was a cross-sectional study and it does not really say anything about the causal link between this map learning and the good cognitive performance or the structural changes of the hippocampus in the brain, because those taxi drivers who managed well in tests might have had a larger hippocampus volume already from the beginning. However, Woollett and Maguire (2011) recently confirmed the findings in a longitudinal study showing that there is a causal link between cognitive training and structural changes of the brain. Similar associations between changes in brain structure after training has also been recently demonstrated by several other researchers and is nicely summarised by May (2011) and Simon, Yokomizo, and Bottino (2012).…”
Section: Lifespan Developmentsupporting
confidence: 67%
“…MRI‐based morphometry has enabled us to noninvasively and quantitatively assess training‐induced structural changes in the healthy adult brain (Best, Chiu, Liang Hsu, Nagamatsu, & Liu‐Ambrose, 2015; Bezzola, Merillat, Gaser, & Jancke, 2011; Draganski et al., 2004, 2006; Engvig et al., 2010; Ilg et al., 2008; Kwok et al., 2011; Landi, Baguear, & Della‐Maggiore, 2011; Schmidt‐Wilcke, Rosengarth, Luerding, Bogdahn, & Greenlee, 2010; Takeuchi et al., 2011, 2014; Taubert et al., 2010; Woollett & Maguire, 2011). For example, Engvig et al.…”
Section: Introductionmentioning
confidence: 99%
“…Draganski et al provided some of the first longitudinal evidence of learning-induced structural plasticity in humans by showing voxel-based morphometric changes in the gray matter of bilateral temporal visual motion areas and the left intraparietal sulcus following three months of training on juggling (Draganski et al, 2004). Additional studies of gray matter have suggested neuroplastic changes resulting from intensive training or learning in domains such as medical knowledge (Draganski et al, 2006), spatial memory (Maguire et al, 2006;Woollett and Maguire, 2011), and aerobic exercise (Colcombe et al, 2006;Erickson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%